Advanced morphological analysis of siloxane‐hydrogel contact lenses - Ţălu, Ştefan (Microscopy research and technique, 2021)
The purpose of this work is to provide a better understanding of three‐dimensional (3‐D) surface texture of siloxane‐hydrogel contact lenses (CLs) using atomic force microscopy (AFM) and stereometric analysis. The 3‐D surface texture characterization of unworn/worn siloxane‐hydrogel CLs made of Filcon V (I FDA group) was performed with stereometric analysis. The atomic force microscopy (AFM) measurements of surface roughness and micromorphology of CLs were made using a Nanoscope V MultiMode (Bruker) in intermittent‐contact mode, in air, on square areas of 5 × 5 μm. Stereometric study of 3‐D surface texture was made according with ISO 25178‐2:2012 for CLrins (taken from the blister and rinsed with deionized water); CLss (preserved for 12 hr in saline solution and rinsed with deionized water); CLworn‐smooth (worn for 8 hr and presenting the smooth type morphology), and CLworn‐sharp (worn for 8 hr and presenting the sharp‐type morphology). The 3‐D surface texture of siloxane‐hydrogel CLs was found to have specific morphological characteristics. Statistical parameters revealed local geometrical and morphological spatial structures at nanometer scale attributed to the specific interactions at the CLs surface. Before wear, the surface micromorphology of Filcon V CLs is regular with uniformly distributed microasperities and relatively small heights (Sq = 0.6 nm). After 12 hr in saline, it is found that the micromorphology changes relatively easily, but retaining the main morphological characteristics (Sq = 1.2 nm). After 8 hr of wear, there are two typical micromorphologies: smooth type, characterized by gutter structures and isolated microasperities (Sq = 2.5 nm), while the sharp type has an appearance with compactly arranged microasperities of hill type flanked by compactly arranged microregions of valley type (Sq = 2.2 nm). Surface statistical parameters allow manufacturers in developing the next generation of CLs with improved surface texture while improving biocompatibility and minimizing the impact of the material on corneal physiology. Furthermore, the micro‐elastohydrodynamic lubrication due to surface texture at a nanometer scale between the back surface of the CL with the corneal surface and the front surface of the CL with the under‐surface of the eyelid can be deeper and more nuanced to understand in light of modern tribological theories. We characterized the surface microtexture of siloxane‐hydrogel contact lens (CLs) using atomic force microscopy and the stereometric parameters. We applied the watershed basin segmentation algorithm for a division into motifs with significant peaks, pits, and shapes of the surface microtexture. The parameters associated with the surface microtexture provide important information to predict and control the dynamic behavior in the tribological interactions of the CL surface with the corneal surface and the lower eyelid surface.